SINGLE PILES SETTLEMENT UNDER THE ACTION OF NEGATIVE FRICTION FORCES - Samorodov, O. V.; Muliar, D. L.; Tabachnikov, S. V. (Academic journal Industrial Machine Building Civil Engineering, 2017)
Nowadays, the use of pile-plate foundations has received extensive development, which takes into account the soil inclusion in the work under its plate part. We proposed a new design of a plate-pile foundation and an engineering method for determining the main parameters of such a foundation, where one of the parameters is the piles settlement under the action of the negative friction forces Pn. As far as is known, field testing of production piles using pressing-in loads is the most reliable method for determining their actual load-bearing capacity. We carried out full-scale tests of a multi-section pile with the loading at depth, on the basis of which a comparative analysis of the settlement of single piles from the action of the negative friction forces, obtained with the help of adapted and existing methods and experimental data